Bioethical aspects of scientific production in medicine from Venezuela 2018–2022 - Brito Nuñez, Jesus; Guerra Di Bonaventura, Paola Estephania; Rivero-Moreno, Yeisson; Naimi Moreno-Brito, Roxana; Alexander Maurera-Diaz, Wilman; Piña, Yasmin; Daniela López-Lezama, Saiddys; Garcia, Andrea; Klaretsy Losada Muñoz, Paola; Daniela Molina-Garcia, Stephanie; et al. (Revista Bioética, 2025)
The approval of projects by an ethics committee, compliance with informed consent and methodological rigor guarantees the reliability of research results and ethical integrity. The objective was to analyze the bioethical aspects of scientific medical production in Venezuela in the Scopus and Web of Science platform considering the 2018–2022 period. A bibliometric analysis of original articles published on research produced in Venezuela was carried out based on approval by a research ethics committee, the origin of the ethics committee, and the declaration of informed consent. Descriptive statistics and association were applied. A total of 523 articles were included, it was found that 50.7% of publications did not declare approval of the project by an ethics committee, 71% were carried out on humans, 69.4% were published in international journals, 44% did not comply with informed consent, and publications from Caracas and Zulia had higher rates of approval by ethics committees.